Pengaruh Lama Waktu Pemeraman Hati Ayam Potong Dengan Arang Aktif Terhadap Zona Daya Hambat Pertumbuhan Bakteri Salmonella thyphi - Hetti Ria Ageru (Poltekkes Kemenkes Yogyakarta, 2010)
Chicken meat has been consumed as one of favorite foods for Indonesian fa-milies. In order to increase the productivity of their livestock, chicken farmer usually give some antibiotics to the chickens via injection, drinking water and feed. Antibiotic residue in chicken liver as an effect of a long period use which did not follow the rule, may affect human health as the consumers. Activated carbon can be used to reduce this residue. The study was aimed to understand the effect of contacting time of the liver with activated carbon by measuring the resistance zone of Salmonella thypi growth in MacConkey agar plate by conducting an experiment with pretest and posttest with control group design. The results show that the widest diameter of resistance zone was found in 2 hour contacting time. However, since the p value derived from Anova test shows weak evidence (p=0,50), it can be concluded that the most effective soaking time is for 3 hour. From the results, it is advised for consumers to process chicken liver into activated carbon prior to cooking it, and subsequent research may be conducted to reveal the saturated time of the carbon.